Epoxy based nanocomposite material for automotive application- a short review - Sakib, Md. Nazmus; Iqbal, AKM Asif (Universiti Malaysia Pahang, 2021)
The automotive industry is a rapidly growing sector of the economy of most countries. Due to consumer and world population growth, the continuous necessity of a better, safe, and economical transportation approach increases with low emission. Researchers and producers face many challenges in the automobile industry for environmental issues, greenhouse gas emissions, boosting the fuel economy, weight minimization, and maintaining modern automobiles' safety and performance. Several strategies towards developing innovative materials have been introduced to address the challenges and replace heavy metal with lightweight polymer composite. Lightweight polymer composite materials offer great potential for increasing vehicle efficiency, decreased fuel consumption, reduced vehicle weight, and corrosion avoidance perspective than heavier materials. Epoxy as a thermoset polymer added with filler material produces nanocomposite material, which increased mechanical, chemical, electrical, and thermal properties, high compatibility, low cost, and shrinkage played significant roles in this regard. This article summarises the material selection process and the application of lightweight polymer composite materials, especially epoxy nanocomposite material, in the automotive industry.